The present state of the leech fauna (Annelida: Hirudinea) in Lithuania - Šatkauskienė, Ingrida; Rutkauskaitė-Sucilienė, Jurgita (Zootaxa, 2022)
The aim of the present study is to present the composition of the leech fauna from Lithuania. Based on morphology, 12 species of leeches belonging to 10 genera and 5 families (Haemopidae, Hirudinidae, Glossiphoniidae, Erpodellidae and Piscicolidae) were identified in the country. Comparison of the data generated in current study with historical records, we extend the list of species to 21. Additional localities of Hirudo medicinalis and Erpobdella monostriata, two uncommon leeches, were established in Lithuania.